"Something There is That Doesn't Love a Wall": Queer Theologies and Reparative Readings†. Issue 1 (January 2015) - Cornwall, Susannah
Abstract : A set of recent conversations among scholars working in queer cultural and literary theory has focused on the trope of reparative reading. Reparative readings, usually contrasted with the "paranoid" criticism of those working in the Butlerian tradition, are often informed by the writings of Eve Kosofsky Sedgwick. This article explores the "reparative turn" in the context of Christian queer theologies, and suggests that it may include practices of "sociability with the dead": both listening to and honouring the abjected past of queer ancestors, and continuing to be in conversation with the damaging and hurtful parts of the Christian tradition as a means of holding them accountable.